Tinjauan Pelaksanaan Program Pemantauan Lingkungan Kerja Fisik dan Kimia di PT. Taka Turbomachinery Indonesia Duri Riau Tahun 2014 - Fentra Welkisam Aidil Fitrah (Lingkungan dan Kesehatan Kerja, 2014)
Work environment monitoring program is a part of Occupational Health and Safety Management System (OHSMS) aimed to help materialize of the maintenance of good employees, so that they are aware of the significance about the implementation of health and safety program for themselves and the company. The applied work environment monitoring program be expected be able to prevent the workers from accidents and occupational diseases. In this study the problems are how does to review the implementation of work environment monitoring programs of chemical and physical at PT. Taka Turbomachinery Indonesia Duri Riau in 2014. The kind of research used in this study is a qualitative approach in order to obtain in-depth information about work environment monitoring program of chemical and physical at PT. Taka Turbomachinery Indonesia Duri Riau. The primary data were obtained by data collection techniques of in-depth interview. The informants for this study there were 4 peoples, namely Site Manager, Supervisor Maintenances, Supervisor Operations, and HSE. From this results be able seen that work environment monitoring program had been carried out each day by PT. Taka Turbomachinery Indonesia Duri Riau at Central Gas Turbine Area. Monitoring of physical work environment by conducting temperature measurement, noise, and radiation. As for monitoring of chemical work environment based on the MSDS. But there are some workers who do not obey with safety rules in the works. The quality of the implementation work environment monitoring program chemical and physical at PT. Taka Turbomachinery Indonesia Duri Riau maintened and further enhanced, in order to create safe work environment. It also needs to be enhanced awareness for workers about the importance of health and safety in the work. Keywords: Work environment monitoring program, physical work environment, chemical work environment